2019
DOI: 10.1016/j.neuroimage.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state white matter-cortical connectivity in non-human primate brain

Abstract: Numerous studies have used functional magnetic resonance imaging (fMRI) to characterize functional connectivity between cortical regions by analyzing correlations in blood oxygenation level dependent (BOLD) signals in a resting state. However, to date, there have been only a handful of studies reporting resting state BOLD signals in white matter. Nonetheless, a growing number of reports has emerged in recent years suggesting white matter BOLD signals can be reliably detected, though their biophysical origins r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
(75 reference statements)
1
23
0
Order By: Relevance
“…We also observed that the correlation coefficients between interconnected GM and WM structures are much higher than those between pairs of GM and WM that are not anatomically connected. This suggests that such coupling is dependent on the structural relationship between GM and WM, supporting the observation of our previous study, based on an animal model and histology, which suggested that functional connectivity shares a similar pattern with the structural connectivity in the GM–WM network ( Wu et al. 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…We also observed that the correlation coefficients between interconnected GM and WM structures are much higher than those between pairs of GM and WM that are not anatomically connected. This suggests that such coupling is dependent on the structural relationship between GM and WM, supporting the observation of our previous study, based on an animal model and histology, which suggested that functional connectivity shares a similar pattern with the structural connectivity in the GM–WM network ( Wu et al. 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…The local engagement map with respect to visual cortex, in contrast, exhibits the highest values in posterior thalamic radiation (including optic radiation) regardless of time delay. The differences in spatial distribution possibly attribute to a notion, which has been demonstrated in an animal model by our previous work ( Wu et al, 2019 ), that BOLD correlations between WM tracts and GM areas are related to their anatomical connections.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, we re‐evaluated the modular organization of the WM functional connectome.We then performed a comparison of topological properties between the WM and GM functional connectomes after regressing out the Euclidean distance matrix from both WM and GM functional connectivity matrices. Global signal effect: we regressed out global brain signals (including WM, GM, and CSF tissues) during WM and GM functional data processing and maintained all other processes to validate the effect of global signals on our findings.After global signal regression, we compared topological properties between WM and GM functional connectomes, as well as between the WM functional connectome and random networks. In addition, we re‐evaluated the topological properties ( E glob , E loc , and σ ) from the test–retest scans. Node parcellation effect: we applied WM bundle masks using the JHU ICBM‐DTI‐81 WM atlas, as has been previously used (Ding et al, ; Wu et al, ) to validate the effects of node parcellation effect on topological property comparisons between the WM functional connectome and random networks. This WM atlas included 48 bundle regions (nodes). CSF signal effect: to further explore the effects of CSF signals, we did not further regress out the brain CSF signals during preprocessing, maintaining all other processes intact.…”
Section: Methodsmentioning
confidence: 99%
“…4. Node parcellation effect: we applied WM bundle masks using the JHU ICBM-DTI-81 WM atlas, as has been previously used Wu et al, 2019) to validate the effects of node parcellation effect on topological property comparisons between the WM functional connectome and random networks. This WM atlas included 48 bundle regions (nodes).…”
Section: Validation Analysesmentioning
confidence: 99%